Comparative Phonology of Malay Languages in West Kalimantan Province: A Dialectological Study - Patriantoro, Patriantoro (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
This research aims to describe and map the phonological correspondence, including any differences, and to create an isogloss file. The conversation method was used for data collection. The technique involved pointing at objects, pictures, photos, and activities. Instruments were used to facilitate data gathering. Data was obtained through in-depth conversations with informants using the prepared instruments. The analysis method used is both descriptive and comparative, employing both quantitative and qualitative descriptive methods as well as the synchronic comparative method. The comparative method is used to compare phonological correspondence differences between observation points. The dialectometric formula was used to calculate the number of phonological differences. The isogloss file is created as the boundary of the Malay language phonological correspondence between observation points. The study results describe the correspondence of Malay language phonology in 13 observation points. Secondly, the phonological correspondence between observation points varies from 6.54% at observation points 1-2 to 14.33% at observation points 9-11. Furthermore, the mapping of the phonological variation and correspondence of the Malay language in West Kalimantan Province revealed the existence of three dialects: Sambas, Mempawah, and Sintang. Figure 2 displays the impact of correspondence and phonological variation on the location of each dialect. Additionally, the isogloss line that distinguishes the phonological correspondence of Malay language variations is represented in the form of isophonic files. This study is significant since it has identified three unique Malay dialects in West Kalimantan and revealed intriguing phonological correspondences among them. The Malay dialects of West Kalimantan exhibit systematic correspondences among the vowels [-e], [-?], [-a], and [-o]. The [o] sound closely resembles the [o] sound in the Malay language of Jambi Province. The Malay dialect of Jambi possesses a variant that concludes with the vowel [o]. This association in West Kalimantan is predominantly observed in the coastal areas of Sambas Regency. This finding suggests that the Malay dialects spoken in West Kalimantan and Jambi are interconnected. The [e] correspondence closely resembles the Malay dialect utilized in Jakarta, particularly in the regions of Sambas, Singkawang, and Bengkayang.